Implementation of Postmethod Pedagogy as an Alternative to Communicative Language Teaching at the Tertiary Level Education - Naushin Nazifa Islam (Center of Language and Cultural Studies [CLCS], 2020)
Along with the subsequent development in the field of English Language Teaching, the idea of methods has been criticized for not being sensitive to the contextual factors and also for being imperialistic in nature. The linguistic and cultural dimensions of archetypal methods establish the culture and language of the native speakers as the only erudite variety by promoting monoculturalism and monolingualism. Furthermore, even in Bangladesh, it can be seen that CLT has been applied as a method to teach English as a foreign/second language since the mid-nineties, but it has not brought any significant changes. Therefore, to overcome the obstacles and limitations experienced by the application of the prototypical methods, the notion of postmethod pedagogy has been introduced which focuses on the significance of contextualized materials to bring authenticity in English language classrooms, which in turn ensures learners’ motivation and successful intake of the lesson. At the same time, it also emphasizes the importance of teacher and learner autonomy. Hence, this research paper explores the scopes of the implementation of postmethod pedagogy and its effectiveness at the tertiary level English language classrooms in Bangladesh.